Sustainability Disclosure and Market Value of Quoted Oil and Gas Companies in Nigeria - Emovon, Felix Osayabor; Izedonmi, Prince Famous (ABUAD Journal of Social and Management Sciences, 2023)
This study has been carried out to examine disclosure and market value of quoted oil and gas companies in Nigeria. The Nigerian oil and gas industry plays a crucial role in fostering economic growth and development. This research employed an ex-post facto research design, with the study population comprising eight (8) publicly listed oil and gas companies on the Nigerian Exchange Group (NEG) as of December 31, 2022. A purposive sampling technique was utilized to select a sample size of seven (7) companies based on data availability. The study spanned from 2012 to 2021, and data were extracted from the annual reports and accounts of the sampled companies on the NEG. Descriptive and inferential statistics were applied to analyze the data, with the testing of hypotheses conducted through panel data regression analysis employing robust cluster standard error. The findings revealed that environmental cost disclosure had a negative and significant impact on market value, while community development cost disclosure had a negative and insignificant effect on the market value of the oil and gas companies. The study concluded that caution should be exercised in disclosures to prevent adverse effects on the firm's market value. Additionally, it recommended that disclosures be closely monitored to avoid negative impacts on the company's market value.